Rice Farming Development Strategi in Rejang Lebong District - Alam, Rizki Rio Jaya; Silamat, Eddy; Pingki, Anadiya; Yanuarti, Mira (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research was conducted in December 2024 to January 2025. This study aims to: 1) the condition of internal and external factors of rice farming in Rejang Lebong Regency 2) Determine alternative strategies for developing rice farming in Rejang Lebong Regency. . The method used in this study is IFE, EFE, and SWOT Matrix Analysis. Respondents selected for the provision of weights and ratings for the IFE and EFE matrices are parties who are competent in research and experts in their fields. The population of this study were stakeholders involved in the agricultural sector of the Rejang Lebong Regency Food Security Service, Lecturers at Pat Petulai University and the Rejang Lebong Regency Agriculture and Fisheries Service. The sampling method was carried out intentionally (Purposive Sampling) with a total of 5 people in each District. In the analysis of internal factors, the IFE matrix analysis showed that the total score obtained was 3.03 while the score results from the internal factors obtained a score of 3.10. The difference between internal factors between strengths and weaknesses obtained a difference of 1.03 and an external factor difference of 0.60, so the SWOT quadrant of the position of rice farming in Rejang Lebong Regency is in an Aggressive strategy condition.